Nature, Origin, and Age Relationships of Landscape Complexes in Southwestern Saskatchewan - Klassen, Rudy (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTSix landscape complexes are recognized in the Cypress Lake (72 F) and Wood Mountain (72 G) areas of southwestern Saskatchewan. The complexes are recognized by their geomorphology, geology, and processes of landscape formation. The relationships of these components are used to determine the relative ages of the complexes. The oldest complex designated “unglaciated bedrock terrain”, consists of mature landscapes developed in Late Cretaceous and Tertiary sediments. It was formed by fluvial and mass wasting processes under Late Tertiary arid to semi-arid climates. A rather similar complex, but with scattered drift residuals - chiefly glacial erratics, is called “bedrock terrain with residual drift”. This complex reflects similar Late Tertiary processes of landscape formation but was later affected by Pleistocene glaciation. A complex called “bedrock terrain and drift” resembles the older complexes except for a veneer of drift and local meltwater channels. Here, effects of the Late Wisconsinan glaciation are restricted to meltwater erosion, and the drift appears to predate this glaciation. The other three landscape complexes are: “first advance drift”, “interlobate drift” and “last advance drift”. These include terrain typical of the parts of the southern prairies covered by the Late Wisconsinan glacier.